KAJIAN BIODIVERSITAS BIOTA LAUT (EKHINODERMATA, MOLUSKA) DI PERAIRAN PULAU PARI, PULAU SERIBU - Sunarto (Jurnal Pro-Life, 2014)
Coastal ecosystems is one of the shallow marine ecosystems are productive, but it is unfortunate that this ecosystem research in Indonesian waters are rare. Where matters relating to the biology and ecology of marine biota (molluscs and ekhinoderms) in the coastal tropical region has not been revealed, including in coastal areas of Pari Island and its surrounding waters. Coastal ecosystem here have the potential of natural resources is very important for the life of the Indonesian nation, which is one member of the United Nations Convention on biodiversity and one of seven countries that have a "Mega Biodiversity' known as the central concentration of the worlds Biodiversitry.ln relation to information about coastal and marine ecosystems in the area location and Surrounding Pari Island waters there is currently no research data, the study, which includes about diversity, distribution and abundance of marine life that live on coastal ecosystems needs to be done. From the results of this study are expected to obtain information about the existence of various types of marine life that can serve as the addition of new collections for the benefit of the scientific world